Respuesta :

Answer:

n = -10

Explanation:

[tex]\Rightarrow \sf \dfrac{1}{n} +\dfrac{4n+16}{n^2-6n} =\dfrac{4}{n-6}[/tex]

Factor the common term

[tex]\Rightarrow \sf \dfrac{1}{n} +\dfrac{4n+16}{n(n-6)} =\dfrac{4}{n-6}[/tex]

Make the denominator same

[tex]\Rightarrow \sf \dfrac{n-6}{n(n-6)} +\dfrac{4n+16}{n(n-6)} =\dfrac{4}{n-6}[/tex]

Join the fractions

[tex]\Rightarrow \sf \dfrac{n-6+4n+16}{n(n-6)}=\dfrac{4}{n-6}[/tex]

simplify the following

[tex]\Rightarrow \sf \dfrac{5n+10}{n(n-6)}=\dfrac{4}{n-6}[/tex]

cross multiply

[tex]\Rightarrow \sf\left(5n+10\right)\left(n-6\right)=n\left(n-6\right)\cdot \:4[/tex]

cancel out common term

[tex]\Rightarrow \sf\left(5n+10\right)=4n[/tex]

exchange sides

[tex]\Rightarrow \sf 5n-4n=-10[/tex]

simplify

[tex]\Rightarrow \sf n=-10[/tex]

ACCESS MORE